2018
DOI: 10.1021/acs.macromol.8b00735
|View full text |Cite
|
Sign up to set email alerts
|

Selective Molecular Transport in Thermoresponsive Polymer Membranes: Role of Nanoscale Hydration and Fluctuations

Abstract: For a wide range of modern soft functional materials the selective transport of sub-nanometersized molecules ('penetrants') through a stimuli-responsive polymeric membrane is key to the desired function. In this study, we investigate the diffusion properties of penetrants ranging from non-polar to polar molecules and ions in a matrix of collapsed Poly(N-isopropylacrylamide) (PNIPAM) polymers in water by means of extensive molecular dynamics simulations. We find that the water distributes heterogeneously in fra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(109 citation statements)
references
References 122 publications
3
94
2
Order By: Relevance
“…Equilibrated molecular structures of the collapsed PNIPAM polymers with water were taken from the previous study [41]. First, 48 polymer chains were solvated in excess water above the transition temperature (≈305 K), which caused the polymers to phase separate from the water phase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equilibrated molecular structures of the collapsed PNIPAM polymers with water were taken from the previous study [41]. First, 48 polymer chains were solvated in excess water above the transition temperature (≈305 K), which caused the polymers to phase separate from the water phase.…”
Section: Methodsmentioning
confidence: 99%
“…Our broader research goal lies in a qualitative molecular-level understanding of thermodynamic and transport properties in PNIPAM-based hydrogels. Employing atomistic, explicit-water simulations, we studied solute partitioning in swollen gels [40] and diffusion inside collapsed gels [41]. In this study, we adopt the previous models to investigate the solvation and partitioning in collapsed PNIPAM polymers of several polar and nonpolar molecules, featuring small alkanes, simple alcohols, and aromatic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…We also showed that in a less hydrated gel, the the diffusion of solutes is lower (i.e., higher ∆F a ) and at the same time the diffusion coefficients indeed decay faster with solute size. 113 In conclusion, all-atom MD simulations offer insights into the molecular nature of the transport and solvation properties of molecules in hydrogels. These mechanisms are not only important for PNIPAM hydrogels, but most probably play important roles also in other responsive hydrogels, and their understanding is important for the rational design of novel materials.…”
Section: Collapsed Statementioning
confidence: 97%
“…9C. Its connected blob-like structure suggests that the diffusion advances via the hopping mechanism 182,183 : A penetrating solute resides for longer time in a local cavity and suddenly performs a longer jump into a neighboring cavity through a transient water channel 113 that forms between the chains (schematically illustrated in the bubbles in Fig. 9C).…”
Section: Collapsed Statementioning
confidence: 99%
See 1 more Smart Citation